Internalization of Religion-Based Character Values Through School Culture at Madrasah Aliyah Negeri of South Bengkulu - Ramedlon Ramedlon; Sirajuddin M; Adisel Adisel; Nurhidayat Nurhidayat; M. Arif Rahman Hakim (STAI Hubbulwathan Duri, 2023)
The purpose of this study is to analyze efforts of cultivation of religious values through school culture at the Madrasah Aliyah Negeri (MAN) of South Bengkulu, describe the support of school culture for disseminating religious values at the MAN of South Bengkulu and identify the factors that influence the application of religion-based character values through school culture at MAN of South Bengkulu. This study uses descriptive qualitative research. The Madrasah head, student advisers, teachers, and students of MAN South Bengkulu provide the most information. This research uses interviews, observations, and documentation. Results of this study: Providing literacy to Islamic religious values, conducting value transactions, and internalising values like worship, discipline, honesty, obedience to rules, responsibility, motivation, keeping the environment clean, tolerance, democracy, togetherness, and caring for others through academic and social culture are examples of value transformation. Second, support a school culture that promotes religious-based character values like praying and trying well, being polite and kind, respecting others, honest in learning, diligent, disciplined, following school rules and teacher rules, self-motivated, and responsible. Third, teachers' active participation in school programmes, competence in their fields, trained teachers and staff with undergraduate to doctoral education, dormitory buildings, etc., influence religious character values in school culture at MAN South Bengkulu.